1994
DOI: 10.1073/pnas.91.26.12887
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of the tissue-specific, developmentally regulated osteocalcin gene requires a binding motif for the Msx family of homeodomain proteins.

Abstract: The OC box of the rat osteocalcin promoter (nt -99 to -76) is the principal proximal regulatory element contributing to both tissue-specific and developmental control of osteocalcin gene expression. The central motif of the OC box includes a perfect consensus DNA binding site for certain homeodomain proteins. Homeodomain proteins are transcription factors that direct proper development by regulating specific temporal and spatial patterns of gene expression. We therefore addressed the role of the homeodomain bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 33 publications
4
106
1
Order By: Relevance
“…Msx2 plays a global role in determination of skeletal mass, elegantly demonstrated in murine genetic models; moreover, as highlighted by Maas and colleagues (15), osteogenic effects during development are dependent upon Msx gene dosage, suggesting that stoichiometry is an important feature of Msx2 action. Consistent with this, we (11, 12, 16 -18) and others (2,19) have shown that Msx2 and Msx1 participate in specific protein-protein interactions that control gene transcription. In the rat OC gene, transcriptional regulation by Msx2 converges on a 42-bp region at nucleotides Ϫ154 to Ϫ113 relative to the transcription initiation site, encompassing an FGF responsive element at nucleotides Ϫ142 to Ϫ136 (17).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Msx2 plays a global role in determination of skeletal mass, elegantly demonstrated in murine genetic models; moreover, as highlighted by Maas and colleagues (15), osteogenic effects during development are dependent upon Msx gene dosage, suggesting that stoichiometry is an important feature of Msx2 action. Consistent with this, we (11, 12, 16 -18) and others (2,19) have shown that Msx2 and Msx1 participate in specific protein-protein interactions that control gene transcription. In the rat OC gene, transcriptional regulation by Msx2 converges on a 42-bp region at nucleotides Ϫ154 to Ϫ113 relative to the transcription initiation site, encompassing an FGF responsive element at nucleotides Ϫ142 to Ϫ136 (17).…”
supporting
confidence: 69%
“…5, 9, 13, and 17), Ku80 (lanes 2, 6, 10, 14, and 20), or BSA (lanes 3, 7, 11, 15, 18, and 21) were used to bind the indicated radiolabeled proteins. The amount of protein bound is referenced to 5% of the input of radiolabeled proteins (lanes 4, 8, 12, 16, 19, and 22), and the relative signal obtained with the known interaction between Ku subunits (lanes [17][18][19][20][21][22]. Note that Msx2 and Runx2 robustly interact with Ku subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms have been proposed to explain how Msx2 counteracts Dlx5. In one model, both factors compete for the same binding site in the target promoters (29,30). Alternatively, interactions between Msx2 and Dlx5 homeodomains may inhibit Dlx5 binding to the target promoters (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, Msx2 also clearly functions to delay the timing of osteoblast terminal differentiation. This is best exemplified by Msx2-dependent suppression of the os-teocalcin (OC) 1 gene in teeth and calvarial osteoblasts (13)(14)(15)(16). During odontogenesis, where stage-specific gene expression programs are spatially resolved, Msx2 and OC are reciprocally expressed (14).…”
mentioning
confidence: 99%